O przestępnym i nieprzestępnym zaniechaniu udzielenia pomocy w niebezpieczeństwie w ujęciu kodeksu karnego z 1997 r. Część II - Kokot, Rajnhardt (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article part two raises the issue of evaluation, under criminal law, of the failure to provide assistance to a person in immediate danger of death or serious injury. It refers to the catalogue issue and legal character of the circumstances defined in Article 162 of the Polish Criminal Code excluding the legal liability in case of failure to provide such assistance. The article analyzes such circumstances and approaches the view of the doctrine and judicature for their interpretation. According to general rules, exemption from legal liability for failing to render assistance draws the line for the entities non-liability, on whom rests that particular, legal duty of concern about the good of the ones in danger guarantor.
Keywords: pomoc; niebezpieczeństwo; brak pomocy; zaniechanie; zagrożenie bezpieczeństwa; narażenie